Explaining Health Disparities between Heterosexual and LGB Adolescents by Integrating the Minority Stress and Psychological Mediation Frameworks: Findings from the TRAILS Study - Kiekens, Wouter; la Roi, Chaïm; Bos, Henny M.W.; Kretschmer, Tina; van Bergen, Diana D.; Veenstra, René (Journal of Youth and Adolescence, 2020)
Lesbian, gay, and bisexual (LGB) adolescents experience elevated levels of internalizing problems and use more substances than heterosexual adolescents. The minority stress and psychological mediation framework are complementary theoretical frameworks that were developed to explain these disparities. However, limited empirical research has integrated both frameworks to study health disparities between heterosexual and LGB adolescents. This study attempts such an integration, using data from the first five waves (participant age 11–22) of the TRacking Adolescents’ Individual Lives Survey (TRAILS), a cohort study of Dutch adolescents (N = 1738; 151 LGB; 54.8% girls). It was tested whether an LGB identity was linked to internalizing problems and substance use through a serial mediation process, in which sexual identity would be associated with peer victimization and negative relationships with parents (first set of mediators, in keeping with the minority stress framework), which in turn would be associated with fear of negative social evaluation and a lack of social support (second set of mediators, in keeping with the psychological mediation framework), and eventually increasing the risk for internalizing problems and elevated levels of substance use. Moreover, it was tested whether the link between minority stress and substance use was mediated by peers’ substance use levels, as hypothesized by the psychological mediation framework. Compared to heterosexual participants, LGB participants reported more internalizing problems, smoked more cigarettes, and used more marijuana, but did not consume more alcohol. The relation between sexual identity and internalizing problems was mediated by peer victimization and parental rejection, which is in line with the minority stress framework. No statistically significant support was found for the psychological mediation framework. These findings provide a better understanding of the pathways through which sexual identity disparities in mental wellbeing and substance use come about.
CRIS-Team Scopus Importer:2025-03-19
Keywords: Adolescents; Internalizing problems; Lesbian; gay; bisexual (LGB); Minority stress; Psychological mediation; Substance use